2014
DOI: 10.1152/ajpcell.00126.2014
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamin-1/TMEM16A is the major apical iodide channel of the thyrocyte

Abstract: Iodide is captured by thyrocytes through the Na ϩ /I Ϫ symporter (NIS) before being released into the follicular lumen, where it is oxidized and incorporated into thyroglobulin for the production of thyroid hormones. Several reports point to pendrin as a candidate protein for iodide export from thyroid cells into the follicular lumen. Here, we show that a recently discovered Ca 2ϩ -activated anion channel, TMEM16A or anoctamin-1 (ANO1), also exports iodide from rat thyroid cell lines and from HEK 293T cells ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 45 publications
2
37
0
2
Order By: Relevance
“…Interestingly, a physiological role for the preference for thiocyanate may exist for these channels, where thiocyanate may be transported across the apical membrane of airway epithelial cells through CaCCs and converted to OSCN − by a combination of oxidases, such as Duox and lactoperoxidase, as an innate immunity defense mechanism against pathogens (38). On the same note, iodide ions are also strongly selected for over chloride, which may be relevant for ensuring proper thyrocyte function in humans and rats (39). In addition to identifying key residues for anion selectivity, we also identified pore blockers with potency that was affected by mutations at these basic residues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a physiological role for the preference for thiocyanate may exist for these channels, where thiocyanate may be transported across the apical membrane of airway epithelial cells through CaCCs and converted to OSCN − by a combination of oxidases, such as Duox and lactoperoxidase, as an innate immunity defense mechanism against pathogens (38). On the same note, iodide ions are also strongly selected for over chloride, which may be relevant for ensuring proper thyrocyte function in humans and rats (39). In addition to identifying key residues for anion selectivity, we also identified pore blockers with potency that was affected by mutations at these basic residues.…”
Section: Discussionmentioning
confidence: 99%
“…More recently,a noctamin (ANO1, TMEM16A) has been suggested to be the dominant iodide transporter at the apical membrane of thyrocytes. [13] This protein was initially characterized as aC a 2+ -activated chloride channel composed of eight transmembrane segments,but displays specificity for iodide.…”
Section: Iodide Uptake and Release Into The Folliclementioning
confidence: 99%
“…However, we demonstrated that SMCT does not transport I − 17 and Slc5a8 KO mice are not hypothyroid 19 . The calcium-activated chloride channel anoctamin1 ( Ano1 ) is expressed at the apical membrane of thyroid follicular cells 20 . HEK 293 T and PCCl3 cells co-transfected with plasmids encoding NIS and Ano1 show increased I − efflux in the presence of ionomycin, a Ca + ionophore, suggesting that Ano1 may play a role in I − efflux 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The calcium-activated chloride channel anoctamin1 ( Ano1 ) is expressed at the apical membrane of thyroid follicular cells 20 . HEK 293 T and PCCl3 cells co-transfected with plasmids encoding NIS and Ano1 show increased I − efflux in the presence of ionomycin, a Ca + ionophore, suggesting that Ano1 may play a role in I − efflux 20 . Ano1 KO mice die within their first month of life and displayed severe tracheomalacia, with gaps in the cartilage rings all along the trachea 21 .…”
Section: Introductionmentioning
confidence: 99%